pbbl Pengembangan Pembelajaran Berbasis Blended Learning (PBBL) Mata Kuliah Sejarah Kebudayaan / Peradaban Islam pada STAIN Parepare - Sewang, Anwar (UI DDI AGH AD Polewali Mandar, 2017)
Blended learning is not only used to increase the student’s learning outcomes, but alsoused to increase the interaction in three learning atmosphere such conventional class, full onlineand combination. This study aims to developed face-to-face, online and offline teaching materialsthat will used in Sejarah Peradaban Islam/Kebudayaan Islam Lesson using Blended Learning basedlearning in three combination such 50/50, 25/75, and 75/25. Subject of this study are the student ofSTAIN Parepare in Sejarah Peradaban Islam/Kebudayaan Islam lesson. There is three class on it.At the end we can conclude that PBBL really need a good quality internet connection. Because, itwill push the students to hard to lesson and give some complicated issue. But, overall PBLL is moreattractive for the student who have a good access for internet connection.